Impact of ambient air pollution on outdoor employees’ performance: Mediating role of anxiety - Bari, Muhammad Waseem; Saleem, Shaham; Bashir, Mohsin; Ahmad, Bashir (Frontiers in Psychology, 2022)
This paper aims to examine the direct and indirect impact of ambient air pollution on employees’ performance. This study has used cross sectional survey design to collect the data from the outdoor employees of the pharmaceutical industry of Pakistan. The data were collected in time lags from 299. Partial least squares- structural equation modeling (PLS-SEM) approach was applied to analyze the data. The results show that ambient air pollution has a significant negative impact on the employees' performance, and anxiety partially mediates the association between ambient air pollution and employees' performance. This study reveals that ambient air pollution brings anxiety among outdoor employees, which in turn decreases their working performance. The implications, limitations, and future research directions are presented in the last section of this study.